Obstetric outcomes and antenatal access among adolescent pregnancies in Kwazulu-Natal, South Africa - Trishka Govender; P Reddy; S Ghuman (South African Family Practice)
Background: Pregnancy among adolescents in South Africa is a growing concern as it may be associated with adverse socioeconomic and health impacts. Timeous initiation and optimal utilisation of antenatal care (ANC) services is imperative to ensure positive pregnancy outcomes. However, this is not always possible owing to various challenges.